2003
DOI: 10.1103/physrevlett.90.228301
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Glass Transition: Beyond Mode-Coupling Theory

Abstract: A new theory for dynamics of concentrated colloidal suspensions and the colloidal glass transition is proposed. The starting point is the memory function representation of the density correlation function. The memory function can be expressed in terms of a time-dependent pair-density correlation function. An exact, formal equation of motion for this function is derived and a factorization approximation is applied to its evolution operator. In this way a closed set of equations for the density correlation funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
132
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(148 citation statements)
references
References 19 publications
5
132
1
Order By: Relevance
“…If this length scale can be unified, then the scalings of the transition densities should automatically coincide (up a constant prefactor). Potential fixes to the standard MCT thus include the generalized mode-coupling theory [47,48], where the factorization approximation of the memory kernel is avoided by explicitly including higher-order dynamical correlations [49], and the mean-field approach proposed in Ref. [24].…”
Section: Discussionmentioning
confidence: 99%
“…If this length scale can be unified, then the scalings of the transition densities should automatically coincide (up a constant prefactor). Potential fixes to the standard MCT thus include the generalized mode-coupling theory [47,48], where the factorization approximation of the memory kernel is avoided by explicitly including higher-order dynamical correlations [49], and the mean-field approach proposed in Ref. [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our approach builds upon the important work of Szamel, who first introduced such a hierarchical scheme of microscopic kinetic equations [24]. Several recent studies have demonstrated that this approach indeed holds great potential as a microscopic theory of glassy dynamics.…”
mentioning
confidence: 99%
“…There are mainly two possibilities for improved idealized MCT, one is given by including hopping processes (due to Gö tze and coworkers [9] as well as Das and Mazenko [10]) and the other is based on new hierarchical closure approximations for the memory kernel by Szamel [11].…”
Section: Introductionmentioning
confidence: 99%